Tőkepiaci versenyképesség tényezőinek alakulása Kelet-Közép-Európában - Katona, Klára (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
The purpose of this paper is to analyse the FDI potential index in Central-Eastern Europe. This index was elaborated by UNCTAD to identify the main elements of competitiveness in capital market. According to international and regional researches these factors influence the investors' decisions which are the following: market size of the country, openness of the trade, state of the infrastructure, level of human capital, country risk, the labour cost and labour productivity, tax policy, tax level. The research covers the periods before and after the integration of this region to European Union. The temporal and spatial comparison concerning the influence of these factors on FDI mirrors the competitiveness of these countries (Hungary, Czech Republic, Slovakia, Poland) in capital market and proved the essential effects of the level of human capital and the infrastructure in the new member states.